Effect of Compaction Pressure and Biomass Type (Rice Husk and Sawdust) on Some Physical and Combustion Properties of Briquettes - Aliyu, M.; Mohammed, I. S.; Lawal, H. A.; Dauda, S. M.; Balami, A. A.; Usman, M.; Abdullahi, L.; Abubakar, M.; Ndagi, B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
In this study, a simple manually operated briquetting machine suitable for use in rural community with no access to electricity supply was fabricated. A three (3) tone hydraulic jack and a pressure gauge were installed to allow for pressure variation. Some physical and combustion properties such as the compressed density, shatter index, hydrophobicity, combustion rate and ignition time of the produced briquettes were determined at the three (3) different compaction pressures of 420.4 kN/m2 , 525.5 kN/m2 and 630.6 kN/m2 . Rice husk (RH), sawdust (SD) and composite briquettes of rice husk and sawdust (RH/SD) were produced using cassava starch as a binder. The developed biomass briquetting machine had a minimum and maximum production capacities of 20 kg/hr and 30 kg/hr respectively. The results showed that the physical properties improved at an increasing compaction pressure. All the produced briquettes at different compaction pressures from the different biomass exhibited over 90% shatter index while the briquette produced from RH at compaction pressure of 525.5 kN/m2 had the highest combustion rate. The RH/SD briquette moulded at compaction pressure of 630.6 kN/m2 had the least combustion rate. The ignition time of the briquettes increased with increasing compaction pressure from 1.28 to 1.58. However, this study found that the RH biomass briquette exhibited a superior solid fuel quality property compared to the other briquette samples. Therefore, this study recommends the RH briquette as a sustainable source of solid biofuel